THE EFFECTS OF SOCIALIZATION, TAX COMPLIANCE, AND TAX COLLECTION ON LAND AND BUILDING TAX REVENUE (PBB-P2) IN THE REGIONAL TAX DIVISION I OF THE REGIONAL REVENUE AGENCY (BAPENDA) OF BATAM CITY - Prastika, Lilis Oktavia; Sabri, Sabri; Sumardin, Sumardin (Yayasan Education and Social Center, 2025)
This study aims to analyze the influence of socialization, taxpayer compliance, and tax collection on Rural and Urban Land and Building Tax (PBB-P2) revenue in Regional Tax Sector I of the Regional Revenue Agency (Bapenda) of Batam City. The study used a descriptive, quantitative approach with a population of 323,830 PBB-P2 taxpayers and a sample of 100 respondents selected via simple random sampling. The instrument, in the form of a questionnaire, has been tested for validity and reliability, with all items demonstrating both. The results of the t-test show that socialization has a significant effect on PBB-P2 revenue (t count = 5.034; sig. = 0.000), taxpayer compliance has a considerable impact (t count = 8.191; sig. = 0.000), and tax collection also has a considerable effect (t count = 7.944; sig. = 0.000). Multiple linear regression analysis yields the equation Y = 5.163 + 0.090X₁ + 0.379X₂ + 0.981X₃, with a determination coefficient (R²) of 0.530, indicating that these three variables explain 53% of the variation in PBB-P2 revenue. The simultaneous F test shows a significant influence of the three independent variables on PBB-P2 revenue (F count = 98.537 > F table = 2.93; sig. = 0.000). This study emphasizes the importance of integrating socialization, compliance, and collection in increasing PBB-P2 revenue in Batam City.